2017
DOI: 10.1016/j.bjorl.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Difficult septal deviation cases: open or closed technique?

Abstract: ENS is as successful as the OTS in management difficult septal deviation cases. In patients with severe septal deformities type of the surgical technique should be selected according to the surgeon's experience and the patient's preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The correction of C-or S-shaped deviated cartilage is difficult, especially in cases with a high deviation. 6) Moreover, if a deviation near the keystone area is removed excessively, the surgeon faces issues due to lack of stability of structures supporting the septum. Therefore, the complete correction of cartilage with high deviation is sometimes difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The correction of C-or S-shaped deviated cartilage is difficult, especially in cases with a high deviation. 6) Moreover, if a deviation near the keystone area is removed excessively, the surgeon faces issues due to lack of stability of structures supporting the septum. Therefore, the complete correction of cartilage with high deviation is sometimes difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, these techniques need an open approach which takes more time and adds the burden of a columellar incision scar, making it difficult to apply unless accompanied by a deviated nose 11 . In a study comparing results of open and closed septoplasty, NOSE scale scores showed better improvement in open septoplasty but without statistical significance 12 …”
Section: Discussionmentioning
confidence: 99%
“… 11 In a study comparing results of open and closed septoplasty, NOSE scale scores showed better improvement in open septoplasty but without statistical significance. 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations